Development of Evaluation and Tests Using the Proprofs Application in Arabic Language Subjects - Uno, Selfiyanti; Hula, Ibnu Rawandhy N.; Tjalau, Cutri (Maharaat: Jurnal Pendidikan Bahasa Arab, 2024)
The advancement of information and communication technology brought significant changes to the field of education, including in learning evaluation. This study aimed to develop an evaluation tool based on the ProProfs application, specifically designed for Arabic language learning, focusing on validity, reliability, feasibility, and practicality. The study employed an R&D method using the ADDIE model, consisting of need analysis, design, development, implementation, and evaluation. The subjects of the study included ninth-grade students and teachers at MTs. Negeri 1 Boalemo. The results indicated that the developed evaluation tool demonstrated excellent validity, with scores of 95% for media and 92% for content. The reliability level was also very high, as shown by an Alpha Cronbach score of 0.924. The implementation of this tool significantly improved students’ learning outcomes, with data showing that 25 out of 30 items were deemed valid, along with optimal difficulty levels and discrimination indices. In conclusion, the ProProfs application proved effective in supporting the evaluation of Arabic language learning, enhancing efficiency and accuracy in assessments while fostering students’ motivation. Adequate facilities, such as computers and internet access in schools, were essential for its implementation. Further research was recommended to expand offline usability features and enrich content to increase its flexibility and benefits.